Get IT going: new ethnic Chinese business. The case of Taiwanese-owned computer rms in Hamburg. - Leung, Maggi W. H. (Journal of Ethnic & Migration Studies, 2001)
Drawing on qualitative, semi-structured interviews with Taiwanese entrepreneurs who operate mostly small- to medium-scale businesses in the computer sales sector in Hamburg (Germany), this paper brings out the diversity of `ethnic entrepreneurship', a notion which is conventionally used almost exclusively for labour-intensive light industries and service-sector activities run by family members or co-ethnics of migrant communities. In order to understand the complex operation strategies of these entrepreneurs, I use the concept of `mixed embeddedness', which emphasises the crucial interplay of the social cultural aspects on the one hand, and that of the local and broader economies on the other. This paper will highlight the importance of developments in production and marketing of the computer hardware industry, the economic conditions in Asia, and the socio-economic environment in Germany in shaping operation tactics, including location rationale, choice of business type and marketing strategies of these enterprises. In addition, the roles of local and transnational ethnic networks in facilitating both business and personal life of these overseas Chinese entrepreneurs in Germany will also be discussed.